2012
DOI: 10.1038/emboj.2012.321
|View full text |Cite
|
Sign up to set email alerts
|

OCT4/SOX2-independentNanogautorepression modulates heterogeneousNanoggene expression in mouse ES cells

Abstract: and SOX2 form the core network of transcription factors supporting embryonic stem (ES) cell selfrenewal. While OCT4 and SOX2 expression is relatively uniform, ES cells fluctuate between states of high NANOG expression possessing high self-renewal efficiency, and low NANOG expression exhibiting increased differentiation propensity. NANOG, OCT4 and SOX2 are currently considered to activate transcription of each of the three genes, an architecture that cannot readily account for NANOG heterogeneity. Here, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
148
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 43 publications
(90 reference statements)
13
148
3
Order By: Relevance
“…This reporter line was also used to assess the effect of transcription factor overexpression. This confirmed that NANOG overexpression increased Esrrb‐GFP expression, and reduced Nanog‐mCherry levels, consistent with autorepression (Navarro et al , 2012). In contrast, ESRRB overexpression showed minimal effects (Fig 1G).…”
Section: Resultssupporting
confidence: 73%
“…This reporter line was also used to assess the effect of transcription factor overexpression. This confirmed that NANOG overexpression increased Esrrb‐GFP expression, and reduced Nanog‐mCherry levels, consistent with autorepression (Navarro et al , 2012). In contrast, ESRRB overexpression showed minimal effects (Fig 1G).…”
Section: Resultssupporting
confidence: 73%
“…It is interesting that Hoxa1 shows occupancy on both the Nanog transcription start site (TSS) and a 4-kb region upstream ( Fig. 2A), which corresponds to a previously identified autoregulatory enhancer (ARE) of Nanog (12). Binding of Nanog and Zfp281 to adjacent sites recruits the NuRD complex and mediates autorepression through this ARE in stem cells to maintain the appropriate levels of Nanog (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Nanog is known to directly activate Oct4 and Sox2, whereas they in turn positively cross-regulate Nanog. Oct4 and Sox2 positively feedback to maintain their own expression via direct autoregulation, whereas Nanog modulates its level of gene expression by negative autoregulation mediated by interactions with Zfp281 (zinc finger protein 281), which recruits the NuRD repressor complex (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Other mechanisms to justify the observed NANOG heterogeneity in mESCs have been proposed, coinciding in the view that fluctuations are controlled at the transcriptional level and emerge from particular configurations of the pluripotency gene regulatory network, involving various types of feedback loops (Niwa et al, 2009;Lanner and Rossant, 2010;MacArthur et al, 2012). For instance, transcriptional autorepression has been proposed to generate fluctuations in Nanog expression (Navarro et al, 2012), whereas other authors propose that these fluctuations result from complex network interactions involving feedback and crosstalk between various signalling pathways and pluripotency TFs (Adachi and Niwa, 2013;Posfai et al, 2014). An intriguing mechanism based on dynamic alleleswitching of Nanog in mESCs has also been proposed to underlie its fluctuations (Miyanari and Torres-Padilla, 2012), although recent evidence does not support a contribution of this mechanism to the observed heterogeneity of NANOG expression in mESCs (Faddah et al, 2013;Filipczyk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%